Temperature modulated DSC studies of melting and recrystallization in polymers exhibiting multiple endotherms - Sauer, B.B.; Kampert, W.G.; Neal Blanchard, E.; Threefoot, S.A.; Hsiao, B.S.
Temperature-modulated DSC (TMDSC)is used to characterize melting and recrystallization in polymers exhibiting multiple melting endotherms. Poly(ethylene-2,6-naphthalenedicarboxylate)(PEN)and poly(oxy-1,4-phenyleneoxy-1,4-phenylenecarbonyl-1,4-phenylene)(PEEK)are chosen, and the data show the detailed contributions of thermal and processing histories to properties. The results are supplemented by standard DSC at different heating rates. By independent very rapid heating rate methods, the temperature at which the polymer first completely flows is used as a measure of the end of melting of crystals originally present in the sample, and is shown to be well below the final DSC melting point because of recrystallization during the DSC heating scan. This is true even for long annealing times at moderately high temperatures. The TMDSC signal detects endothermic peaks or shoulders corresponding to the melting of crystals originally present in the sample, and such information are not available from standard DSC because of offsetting exothermic and endothermic signals. The TMDSC data prove that the "low endotherm"-routinely detected by standard DSC a few degrees above isothermal annealing temperatures-is not a true "low endotherm", but is a superposition of early melting of secondary crystals with almost simultaneous exothermic recrystallization. It is not a distinct endotherm because the degree of recrystallization measured in the non-reversing signal of TMDSC increases continuously up to and sometimes through the final melting region. This description of the thermal scan considers both primary crystals, secondary crystals, and recrystallization during the heating scan.
Keywords: TEMPERATURE-MODULATED DSC (TMDSC); POLY(ETHYLENE-2,6-NAPHTHALENEDICARBOXYLATE)(PEN); POLY(OXY-1; 4-PHENYLENEOXY-1; 4-PHENYLENECARBONYL-1,4-PHENYLENE)(PEEK)